2019
DOI: 10.1177/0960327119886037
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration with tetrahydrocannabinol causes retinal damage in BALB/c mice

Abstract: Recent years have seen substantial shifts in cultural attitudes towards cannabis for medical and recreational use. However, legalizing recreational marijuana may have adverse effects on individual and public health. As the most widely used illicit agent, cannabis is commonly reported to disrupt learning and memory. Unfortunately, the molecular mechanisms underlying behavioral impairment by cannabis abuse remain poorly understood. Tetrahydrocannabinol (THC), a major component in cannabis, causes short-term effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…An experimental study using adult BALB/c mice showed that 2-month treatment with intraperitoneal injection of THC caused functional retinal impairment and increased apoptosis in photoreceptors by induction of inflammatory response and oxidative stress. Although the via of administration of THC was different from our study and retinal damage was detected directly in the exposed mice, these are evidences that the use of Cannabis induces an inflammatory state in the retina and it might be related to morphological changes [ 30 ]. In our study it is not possible to correlate the morphological changes in young adult and adult mice with functional retinal changes as the design of the study does not allow conclusions to be drawn in this regard.…”
Section: Discussioncontrasting
confidence: 60%
“…An experimental study using adult BALB/c mice showed that 2-month treatment with intraperitoneal injection of THC caused functional retinal impairment and increased apoptosis in photoreceptors by induction of inflammatory response and oxidative stress. Although the via of administration of THC was different from our study and retinal damage was detected directly in the exposed mice, these are evidences that the use of Cannabis induces an inflammatory state in the retina and it might be related to morphological changes [ 30 ]. In our study it is not possible to correlate the morphological changes in young adult and adult mice with functional retinal changes as the design of the study does not allow conclusions to be drawn in this regard.…”
Section: Discussioncontrasting
confidence: 60%
“…Additionally, in a retinal damage study, daily administration of THC (1 or 2 mg/kg) for two months induced a significant increase in oxidative stress, manifested by an increase in malondialdehyde (MDA) levels, a decrease in reduced glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT) activity and an increase in NOX-4 protein expression. In addition, there was an increase in nitric oxide, IL-1β, IL-6, and TNF-α production in mouse retina [108]. In a study on the pancreas, the effects of THC were investigated in rats with hyperinsulinemia.…”
Section: Role Of Cannabis Compounds In Neurological and Systemic Infl...mentioning
confidence: 99%
“…Contrary to the studies mentioned, some models also reported neurodysfunctional effects due to cannabinoids and their receptors. Two months of systemic treatment with Δ 9 -THC resulted in toxic effects on photoreceptor cells in mice through functional loss in electroretinography and apoptosis [ 148 ]. For a detailed overview of other studies on neuroprotection in ocular diseases, the reader is referred to more extensive reviews [ 9 , 20 , 60 ].…”
Section: Neuroprotective Actions Of Cannabinoidsmentioning
confidence: 99%